School break: what happens far from the teachers’ eyes? - Neuenfeld, Derli Juliano (Journal of Physical Education (Maringá), 2008)
This research aimed at verifying which activities students attending the 1st to 4th grades of the fundamental school practice during school break. The investigation was developed at Duque de Caxias Municipal Fundamental School in Santa Cruz do Sul city/state of Rio Grande do Sul/Brazil. The school break routine, the children activities and their relation with both the physical area and the available material were evaluated. It was concluded that children spent most of their break time having a snack, and that the physical space of the sportive courts lead children to play under the performance sport model. That makes us to argue: would it be interesting to develop a pedagogical intervention during this school break?